Arbitrary Ca2+ regulation for endothelial nitric oxide, NFAT and NF-κB activities by an optogenetic approach - Tomoyasu Yamanaka; Takatoshi Ueki; Mitsuhito Mase; Koichi Inoue (Frontiers Media S.A., 2023)
Modern western dietary habits and low physical activity cause metabolic abnormalities and abnormally elevated levels of metabolites such as low-density lipoprotein, which can lead to immune cell activation, and inflammatory reactions, and atherosclerosis. Appropriate stimulation of vascular endothelial cells can confer protective responses against inflammatory reactions and atherosclerotic conditions. This study aims to determine whether a designed optogenetic approach is capable of affecting functional changes in vascular endothelial cells and to evaluate its potential for therapeutic regulation of vascular inflammatory responses in vitro. We employed a genetically engineered, blue light-activated Ca2+ channel switch molecule that utilizes an endogenous store-operated calcium entry system and induces intracellular Ca2+ influx through blue light irradiation and observed an increase in intracellular Ca2+ in vascular endothelial cells. Ca2+-dependent activation of the nuclear factor of activated T cells and nitric oxide production were also detected. Microarray analysis of Ca2+-induced changes in vascular endothelial cells explored several genes involved in cellular contractility and inflammatory responses. Indeed, there was an increase in the gene expression of molecules related to anti-inflammatory and vasorelaxant effects. Thus, a combination of human blue light-activated Ca2+ channel switch 2 (hBACCS2) and blue light possibly attenuates TNFα-induced inflammatory NF-κB activity. We propose that extrinsic cellular Ca2+ regulation could be a novel approach against vascular inflammation.